IMPLIKASI YURIdIS dIUNdANGKANNYA UNdANG-UNdANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN dAERAH TERHAdAP PENGATURAN BAdAN USAHA MILIK dAERAH dI INdONESIA - Made Gde Subha Karma Resen; Yudho Taruno Muryanto (Faculty of Law, Universitas Sebelas Maret, 2014)
The enactment of Law Number 23 Year 2014 on Regional Government has implications for setting local owned enterprises (BUMD) in Indonesia. Law No. 23 Year 2014, revoke Law Number 5 of 1962 and Law Number 32 Year 2004, the previous both are the legal basis for setting local owned enterprises in Indonesia. In Law No. 23 Year 2014, specifically regulates the local owned enterprise, namely in Chapter XII, consisting of 12 Articles, starting from Article 331 to Article 343 and scattered in several chapters, Article 1 paragraph 40, Article 134 paragraph (1) letter c, 188 paragraph (1) c, subsection 298 (5) c,subsection 304 (1) and (2), 320 (2) g, 402 paragraph (2), 405 and Article 409.